Socio-economic impact of HIV/AIDS and compounding effect of COVID-19 pandemic in sub-Sahara Africa - Julius, Mekolle, Enongene (My University, 2022)
Together with the recent emergence of COVID-19, which is not only directly contributing to high morbidity and mortality but is also destabilizing critical health systems and undermining HIV and other global health initiatives, the spread of HIV/AIDS has adversely impacted all advancements in education, health, standards of living, and life expectancy that Africa has made since the 1950s. However, all nations and regions must work together to find solutions to these global issues, especially sub-Saharan Africa, which has the lowest vaccination rates worldwide and the highest rates of HIV/AIDS infection despite having promising economic possibilities. The goals of this review were to emphasize the effects of HIV and AIDS on socio-economic development in sub-Saharan Africa and to highlight how the COVID-19 pandemic affects this relationship.
Keywords: COVID-19; HIV/AIDS; Socio-economic impact; sub-Sahara Africa